Digital Communication & Socialization Using Media Video Content During Pandemic - Valentina, Anny; Chrissandy, Ruby; Jesslyn, Brigitta; Setyanto, Yugih (Jurnal Komunikasi, 2022)
A continuation research about the media used by human to communicate during PSBB period. This content of this research is about type of creative contents that can be used on social media. From the previous research, it was found that, in order to survive during pandemic and to live their daily lives, human need socializing and entertainment. Those are two important things for them. The purpose of this research is to find out types of media and digital content that are not only interesting to the respondent but also effective in conveying the communication message and can be utilize as a socialization platform. The concept of "social-media forum" which is applied to the published contents is considered different from other content in general. When the speaker invited is a person who also experiencing the same problem, audience interprets them as a friend who understand the problem and their feelings deeply, and from this angle it is hoped that the speaker and the audience can start to bond to exchange stories and opinions, not particularly about the solutions but might be just a perspective from different angle. However, doing this in virtually because of pandemic is tiring, all parties involved felt extreme fatigue after the event was over. It is because virtual meetings force human brain and body to put more focus and more alert for a long time, in the end, even casual conversation feels tiring. The samples taken for this research are located in Jakarta, focused to 20-29 years old  men and women. Data collection method is using qualitative approach with observation techniques, literature study, FGD, and interviews. When situations force us to shift into the digital and virtual realms, a recommendation for creative content format for screen-based social media is needed to be studied further, resulting in all parties involved do not have to feel an extreme fatigue but can become a useful communicator who offers solutions to others.